Identification of barriers to insulin therapy and approaches to overcoming them. Issue 3 (22nd November 2017) - Russell‐Jones, David; Pouwer, Frans; Khunti, Kamlesh
Abstract : Poor glycaemic control in type 2 diabetes (T2D) is a global problem despite the availability of numerous glucose‐lowering therapies and clear guidelines for T2D management. Tackling clinical or therapeutic inertia, where the person with diabetes and/or their healthcare providers do not intensify treatment regimens despite this being appropriate, is key to improving patients' long‐term outcomes. This gap between best practice and current level of care is most pronounced when considering insulin regimens, with studies showing that insulin initiation/intensification is frequently and inappropriately delayed for several years. Patient‐ and physician‐related factors both contribute to this resistance at the stages of insulin initiation, titration and intensification, impeding achievement of optimal glycaemic control. The present review evaluates the evidence and reasons for this delay, together with available methods for facilitation of insulin initiation or intensification.